Competitive and comparative advantage of ruminant meat and its import determinants in Malaysia - Mohd Yusoff, Hebat Hisham (2021)
Malaysia’s self-sufficiency level for ruminant meat has never exceeded 30 percent for the past 10 years despite various intervention measures introduced by the government to overcome the issue. The increasing demand of ruminant meat in Malaysia triggered by the economic and socio factors has not been matched by the ability of domestic production. The situation has created over dependency on import as to cover the shortage. However, the sources of import are currently confined to Australia, New Zealand and India. This over-dependency on limited number of countries has put Malaysia in a vulnerable situation due to the exposition of supply disturbance. Malaysia’s dependency on import in fulfilling its need for ruminant meat is not something that could be addressed instantly. Even in the situation that Malaysia is able to meet the targeted self-sufficiency levels of 30 percent, it will not entirely put a stop to the import dependency as the deficit will still be addressed through importation. In this regard, various intervention programs have been introduced by the government to boost up the domestic production. Despite the intervention programs which are specifically targeted to increase the availability of ruminant meat in the country, the issue of low selfsufficiency level still persist. The objective of this study is to examine the competitive advantage of the trading partners on the exportation of ruminant meat. Besides that, this study also identify factors that explain the import of ruminant meat and also determine the comparative advantage of local production of ruminant meat. This study employs Vollrath indices through the utilization of relative export advantage, relative import advantage and ultimately the overall relative trade advantage for the first objective. Analysis has been conducted on 26 countries and 15 product codes of ruminant meat. As for the second objective, gravity model has been employed and panel data of 19 countries, 15 product codes of ruminant meat and import data of 10 years have been tested and estimated. Pooled Ordinary Least Square (POLS), Random Effect Model (REM) and Fixed Effect Model (FEM) were utilized as an estimator but focus of analysis was based on Pooled Ordinary Least Square. Policy Analysis Matrix (PAM) has been adopted for the third objective based on the survey conducted on 29 cattle farms operated under the program of Taman Kekal Pengeluaran Ruminan (TKPR). The findings of this study indicate that the possession of competitive advantage is not exclusively belonged to the traditional sources, but other countries as well particularly Pakistan and Netherland. Besides that, the findings for factors that explain Malaysia’s import have found that halal certification play a significant role in influencing import. Its importance has outweighed other single economic factors that include geographical distance, memberships of free trade agreement (FTA), gross domestic product (GDP) as well as endowments. The results from Policy Analysis Matrix (PAM) have suggested that the comparative advantage of ruminant sector in Malaysia is largely dependent on the type of farms adopted by the farmers.